Hematoporphyrin derivative-photodynamic therapy (HpD-PDT) for extensive vulvar and vaginal Bowen's disease: A case report - Xiaoqing Xiang; Yanliang Li; Can Shi; Runqun Liu; Guozhang Ma; Yunyun Cao; Lianheng Xia; Jie Gao (Photodiagnosis and Photodynamic Therapy)
Bowen's disease (BD) is an intraepithelial squamous cell carcinoma (SCC) that commonly affects older individuals, with the vulva being a prevalent site in women. Lesions within the vagina pose a particular challenge for surgical treatment, often compromising both functional integrity and cosmesis. Photodynamic therapy (PDT) is an emerging, safe, and non-invasive technique utilizing a photosensitizer and a specific light source, widely applied in the treatment of malignancies and skin diseases. We report the case of a 74-year-old woman presenting with a large, dark brown patch on the vulva, histopathologically confirmed as BD. The patient also had lesions within the vagina. Hematoporphyrin derivative-photodynamic therapy (HpD-PDT) was administered, with an optical fiber used for targeted treatment of the vaginal lesions. Complete resolution of the lesions was observed after a single treatment. A follow-up biopsy at 7 months post-treatment revealed no residual tumor cells. The patient remains disease-free at 2 years follow-up and continues to be monitored. This case suggests that HpD-PDT is a viable treatment option for BD, and may be particularly advantageous for elderly patients with extensive or vaginally located lesions, where preserving function and cosmesis is paramount.